Crystalluria with Systemic Hypertension and Suspected Right Ventricular Dilatation in a Pug Dog - I Gusti Bagus Aryanta Kusuma Putra; Putu Ayu Sisyawati Putriningsih; Putu Devi Jayanti; I Putu Gede Yudhi Arjentinia (Journal of Applied Veterinary Science And Technology, 2026)
Background: Activity of the Renin-Angiotensin-Aldosterone system (RAAS) may be influenced by renal disorders, potentially contributing to the development of systemic hypertension. Persistent hypertension increases cardiac workload and may lead to structural cardiac changes, including ventricular dilation and cardiac remodeling.  Purpose: Description is provided herein regarding the diagnostic findings and therapeutic management of crystalluria associated with systemic hypertension and suspected right ventricular dilatation in a dog. Case (s): Presentation of a 2.5 year old female Pug dog weighing 5.85 kg was made with a seven-month history of white urine residues and a two month history of stranguria. Identification of white deposits around the vulva, pain upon urinary bladder palpation, and rhonchi on thoracic auscultation was made during physical examination. Urinalysis revealed numerous struvite crystals, proteinuria (+++), a urine pH of 7, and a specific gravity of 1.015, while lymphocytopenia was demonstrated via hematological examination. Detection of sediment in the urinary bladder and hyperechoic structures in the renal medulla was achieved through ultrasonography. Furthermore, rounding of the right cardiac border was observed on thoracic radiography, and right ventricular thickening with possible dilation was suggested by echocardiography. Marked hypertension (191/167 mmHg) was confirmed through blood pressure measurement. Case Management: Therapeutic intervention consisted of amoxicillin clavulanic acid (12.5 mg/kg orally twice daily for 7 days), enalapril maleate (0.5 mg/kg orally once daily for 7 days), a urinary tract supplement containing N-acetyl-D-glucosamine (½ capsule orally once daily for 14 days), and dietary management utilizing a renal support diet. Significant clinical improvement and normalization of blood pressure were observed after 14 days of treatment, although a residual presence of struvite crystals in the urine sediment was noted. Conclusion: After 14 days of treatment, the clinical condition improved and blood pressure returned to within normal limits, although a reduced number of struvite crystals remained in the urine sediment.